2015
DOI: 10.5194/bg-12-1849-2015
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic carbon from tropical savanna burning: production and stable isotope composition

Abstract: Abstract. Widespread burning of mixed tree-grass ecosystems represents the major natural locus of pyrogenic carbon (PyC) production. PyC is a significant, pervasive and yet poorly understood "slow-cycling" form of carbon present in the atmosphere, hydrosphere, soils and sediments. We conducted 16 experimental burns on a rainfall transect through northern Australian savannas with C 4 grasses ranging from 35 to 99 % of total biomass. Residues from each fire were partitioned into PyC and further into recalcitrant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 63 publications
1
50
0
Order By: Relevance
“…If forests that historically experienced lower-severity fires (e.g., surface fires) undergo shifts in disturbance regimes to include high-severity fire (e.g., canopy fire) as is already the case in many forests of the western U.S. [20,21,44,45], we suggest that a greater proportion of the aboveground forest may be converted to PyC. Although it has been suggested the PyC produced during a fire may be consumed in subsequent fires [46], recent studies have found limited PyC consumption in subsequent fires [47,48]. Thus, the effects of climate change on fire regimes may lead to increased PyC stocks produced in each forest fire.…”
Section: Discussionmentioning
confidence: 66%
“…If forests that historically experienced lower-severity fires (e.g., surface fires) undergo shifts in disturbance regimes to include high-severity fire (e.g., canopy fire) as is already the case in many forests of the western U.S. [20,21,44,45], we suggest that a greater proportion of the aboveground forest may be converted to PyC. Although it has been suggested the PyC produced during a fire may be consumed in subsequent fires [46], recent studies have found limited PyC consumption in subsequent fires [47,48]. Thus, the effects of climate change on fire regimes may lead to increased PyC stocks produced in each forest fire.…”
Section: Discussionmentioning
confidence: 66%
“…Saiz et al (2015a) conducted 16 experimental fires across a broad range of savannas in NE Australia, and showed that <10% of the total PyC produced by biomass burning in those ecosystems is emitted into the atmosphere as particles capable of moving far from the site of production, while a much larger proportion remains (initially) close to the site of production. PyC remaining on the ground may subsequently be re-mineralised by biotic and/or abiotic processes, be re-combusted in subsequent fire events, be exported in dissolved or particulate form, and/or accumulate in the soil or in the sedimentary record (Bird et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the carbon isotope composition of PyC is amenable for use in fire reconstructions, particularly in savanna environments, as it represents one of the main tracers capable of providing a fingerprint of the type of vegetation being burnt (Bird et al, 2015). Indeed, the contrasting δ 13 C values of tropical grasses, which primarily use the C 4 photosynthetic pathway (δ 13 C > −15‰), and woody vegetation, all having the C 3 photosynthetic pathway (δ 13 C < −24‰) allow for a discrete differentiation of the precursor biomass in studies assessing PyC in mixed C 3 /C 4 ecosystems (Saiz et al, 2015a). There are however, potential complications limiting the interpretation of the isotopic signal, which includes isotopic fractionation effects associated with the production of PyC during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion rates also vary across forest components, as low as 7.3% for conifer needles to 67.1% for bark in a boreal jack pine fores (Santín et al, 2015b). Saiz et al (2015) estimated a 16% conversion rate for surface fuels across contrasting tropical savannas using visual, gravimetric and total C identification. Differences among ecosystems and among quantification methodologies contribute to the variability of these results.…”
Section: Introductionmentioning
confidence: 99%